1984
DOI: 10.1016/0009-3084(84)90063-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the zymogen of phospholipase A2 binds to a negatively charged lipid-water interface

Abstract: Evidence is presented that the zymogen of porcine pancreatic phospholipase A~ (prophospholipase A2) interacts with a lipid-water interface provided that the interface has a net negative surface charge. Fluorescence spectroscopy and non-equilibrium gel filtration indicate that binding of prophospholipase A 2 (proPLA) to mixed detergent micelles is dependent on the presence of an anionic detergent. Prophospholipase binding is accompanied by a change in the environment of the single tryptophan residue qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…It should be noted that the change in the intensity in the difference spectrum reflects the fraction of the enzyme in the E*−MJ33 form, while the shape of the difference spectra, in particular, peaks at 288 and 292 nm, is attributed to the Trp3 environment. These difference spectra for PLA2 or proPLA2 binding MJ33 at the interface are strikingly similar to those observed by the Utrecht group ( , ) with the enzyme binding to SDS. The intensity change at 292 nm as a function of the mole fraction of the inhibitor () suggests that the affinities of MJ33 for PLA2 and proPLA2 are not significantly different.…”
Section: Resultssupporting
confidence: 86%
“…It should be noted that the change in the intensity in the difference spectrum reflects the fraction of the enzyme in the E*−MJ33 form, while the shape of the difference spectra, in particular, peaks at 288 and 292 nm, is attributed to the Trp3 environment. These difference spectra for PLA2 or proPLA2 binding MJ33 at the interface are strikingly similar to those observed by the Utrecht group ( , ) with the enzyme binding to SDS. The intensity change at 292 nm as a function of the mole fraction of the inhibitor () suggests that the affinities of MJ33 for PLA2 and proPLA2 are not significantly different.…”
Section: Resultssupporting
confidence: 86%
“…It is of interest that when proPA2 was titrated with either single-chain or double-chain anionic substrate analogues, only a relatively small perturbation of the Trp environment was observed from the phosphorescence spectra and the ODMR transition frequencies. This agrees with the results obtained by Hille et al (1983a) andVolwerk et al (1984); the zymogen of porcine PA2 interacts with anionic or negatively charged mixed detergent micelles, but the extent of the perturbation of the single Trp environment is less than that found for the active enzyme.…”
Section: Discussionsupporting
confidence: 91%
“…In these "pseudomicellar" complexes only PA2 but not the zymogen becomes superactivated. A related observation is that of Volwerk et al (1984), who found that titration of PA2 with SDS-containing C16-PN micelles leads to a large (ca. 200%) increase in fluorescence, whereas only a relatively small (less than 50%) fluorescence enhancement is found by using proPA2.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…If the decrease in dynamic freedom found for Trp-3 also occurs for other residues, the decrease in configurational entropy for ProPLA2 upon binding may be of sufficient magnitude to prevent complex formation. Recent studies indicate that ProPLA2 can bind to negatively charged micelles (Volwerk et al, 1985). In this case, the electrostatic interaction of the negatively charged lipids with positively charged residues on the surface of ProPLA2 may compensate for any loss of configurational entropy that binding entails.…”
Section: Discussionmentioning
confidence: 99%